Comparison of Topical Skin Adhesive and Simple Interrupted Nylon Sutures for Wound Closure in Forefoot Surgery: A Prospective Randomised Trial. Issue 4 (22nd October 2020) - Ray, Robbie; Goff, Thomas A.; Dearden, Paul M.; Robinson, Peter W.; Lam, Peter; Wines, Andrew P.; Lewis, Thomas L.
Category: Bunion Introduction/Purpose: There are many options for wound closure in forefoot surgery. The purpose of this study was to compare topical skin adhesive (2-Octyl-cyanoacrylate) to standard simple interrupted nylon sutures with attention to the quality of wound healing and the acceptability to the patient. Methods: Patients undergoing elective 1st ray forefoot surgery utilising a medial incision, either Hallux Valgus correction or 1st Metotarsophalangeal joint arthrodesis, were recruited to this study. Patients were randomly allocated during surgery to final layer wound closure with either the intervention topical skin adhesive (TSA) or the control interrupted nylon sutures (INS). Practicality was assessed by time taken for wound closure and subsequent time to perform wound care at 2 weeks postoperatively, wound care pain (VAS) and quality of wound healing was assessed at this point with a dedicated scoring tool, patient satisfaction and acceptability was assessed at 6 weeks postoperative. Results: 70 patients (18 bilateral) were recruited, resulting 42 feet in each study group (after 4 exclusions for incomplete data set). Mean age 61 (29-83). There were no statistical differences in the demographics or surgery performed between groups. Wound closure time was significantly slower for TSA (272 secs (SD 72.2) vs 229 secs (SD 58.8), p=0.0038). At 2 weeks postoperative wound care time was significantly faster for TSA (71 secs (SD 50.8) vs 120 Secs (SD 47.8), p<0.0001), and patient reported pain was significantly less with TSA (VAS 0 vs 2, p=0.025). Significantly more inflammation and wound edge separation was recorded with TSA (17 vs 5 cases, p=0.006) and (12 vs 3 cases, p=0.02) respectively. High satisfaction was reported in both groups with no signifcant difference. Conclusion: Topical skin adhesive and interrupted nylon sutures are both acceptable closure methods for forefoot surgery with high satisfaction rates, low pain scores and low complications. However, the observation of significantly more inflammation and areas of wound separation at the early post-operative period with topical skin adhesive is sufficient to recommend routine use of sutures.